Current Developments in the Prevention and Improvement of Intestinal Disorders: A Mini-Review - Santa, Kazuki; Ohsawa, Tomonori (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
Recently, the number of patients who manifest intestinal disorders has increased. Particularly, Irritable Bowel Syndrome (IBS) patients and Inflammatory Bowel Disease (IBD) patients, which include Ulcerative Colitis (UC) and Crohn’s Disease (CD), are on the rise, especially in the young generation. Behcet’s disease (an autoimmune disease) and bowel obstruction are also common intestinal disorders. Furthermore, colorectal cancer, including colon and rectum cancer and small intestinal cancer, are the typical disorders in the intestine. Other disorders in the digestive tract are infectious diseases like Helicobacter pylori infection. Even though symptomatic treatments have been increasing for the treatment of intestinal disorders, the ways of improving and preventing these diseases are still controversial.The progress of medicine and treatment is rapid. However, recent approaches to the prevention and improvement of these intestinal disorders are suppressing dysbiosis and preventing chronic inflammation. This mini-review discusses the hypothesis of whether the improvement of the diet is a preferable choice for the prevention of these intestinal disorders. Dietary interventions are beneficial for the prevention and improvement of intestinal disorders since the first approach to intestinal disorders is dietary intervention. The Mediterranean diet, the diet from the 5-a-day campaign, and the Japanese diet are well-known healthy dietary strategies. A healthy diet regimen is not only beneficial for the prevention of intestinal disorders but also a useful strategy to reduce stress and ameliorate mental illness. In addition, the intake of phytochemicals is good for keeping healthy gut microbiota and preventing intestinal disorders. Furthermore, vitamin D3 intake with these phytochemicals works as an adjuvant to improve gut microbiota and upregulate immune responses. As a result, the decreasing production of TNF-α ameliorates chronic inflammation and intestinal disorders at an early stage.In recent years, prevention of the non-disease condition “ME-BYO” has been a popular approach for healthy and long living in Japan. This idea prevents the manifestation of diseases before the onset and is also applicable to intestinal disorders. This mini-review discusses ways of preventing and ameliorating intestinal disorders.
Keywords: Intestinal disorders